Numerical study on movements of soil particles forming clogging layer during vacuum preloading of dredged slurry - Shi, Li; Jiang, Jianwei; Wang, Qiuqi; Sun, Honglei; Yuan, Zonghao; Pan, Xiaodong (Granular matter, 2021)
A clogging layer would be formed on surface of the prefabricated vertical drain (PVD) when the dredged slurry is treated using the vacuum preloading method. The clogging layer decreases the efficiency of drainage consolidation seriously. A numerical model is built to study the slurry particle movements and the resulting clogging layer of the vacuum-treated slurry, by adopting the discrete element method (DEM) and the computational fluid dynamics (CFD) for describing the slurry particles/PVD membrane and the pore water, respectively. The effectiveness of the CFD-DEM solver and the numerical model is verified through comparisons to the analytical solution of single-particle settling problem and to PIV (particle image velocimetry) test results on slurry particle displacements. Characteristics of movements associating with particles of different size and locations within the clogging layer are compared and analyzed. It is found that the maximum velocity and the final displacement of particle of larger size are generally larger. The displacement of particle, when its motion finally ceases, increases with the distance between its initial location and the PVD membrane. Particles of larger size stop moving firstly and form the skeleton of the clogging layer; while particles of smaller size keep moving within the skeleton, and thus render the clogging layer more compacted.